A atuação do judiciário gaúcho no controle e fiscalização de guarda e depósito de animais silvestres - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The purpose of this Course Completion Work is to analyze the performance of the Rio Grande do Sul judiciary in controlling and supervising the custody of wild animals, based on Federal Law 9,605/1998 (Environmental Crimes Law), as well as on jurisprudence collected before the Court of Justice of Rio Grande do Sul (TJRS). The method chosen for the development of the project in question was the deductive method, as it starts from a general conception for a more specific elaboration, first addressing the classification of animals, the institute of custody in Environmental Law, the analysis of the institute of the faithful depositary and ending with the action of the Rio Grande do Sul judiciary in some cases involving wild animals. The methodology chosen for this research is applied research, with the main focus being to generate knowledge for practical application, also using a qualitative approach, eliminating the need for interviews or third-party surveys. In this sense, the research on screen has an explanatory nature, from the point of view of its objectives, thus aiming to deepen knowledge, analyze jurisprudence and legislation, demonstrating the performance of the Gaucho judiciary and its cooperation with some entities and institutions, with the objective to ensure and protect the fauna and flora of the Pampa Gaúcho biome.
The role of the Rio Grande do Sul judiciary in controlling and supervising the custody and storage of wild animals
Keywords: Fauna silvestre; Crimes ambientais; Judiciário gaúcho; Gaucho judiciary; Environmental crimes; Wild fauna; CNPQ::CIENCIAS SOCIAIS APLICADAS